(untitled) (Value : Jurnal Manajemen dan Akuntansi, 2025)
Capital expenditure is a form of capital creation, which includes investments and expenditures made to acquire or develop assets with an expected economic return period of more than one year. The aim of this research is to determine the effect of capital expenditure on local revenue (PAD) and balancing funds in districts/cities in West Sumatra Province in 2019-2023. The research method used is a quantitative research method. This data comes from the following websites: https://www.bps.go.id/ and https://djpk.kemenkeu.go.id/, which are managed by the Indonesian Directorate General of Financial Balance (DJPK). This research uses 95 reports covering the years 2019-2023 covering districts/cities in West Sumatra province, to examine the realization of local original income, balancing funds, and district/city capital expenditures in West Sumatra province, namely using the Econometric Views (EViews) version of the software. 10 using descriptive statistical tests, model feasibility, classical assumptions, panel data regression, hypotheses, and the Adjusted R Square coefficient test used in data analysis. The findings of this study confirm the null hypothesis that balancing funds do not influence capital expenditure positively and significantly, but local revenue influences capital expenditure positively and significantly.